Konstitusionalisme dan Hak Asasi Manusia - Marzuki, Laica (Jurnal Konstitusi, 2011)
The Constitution is not the main topic. The Constitution itself does not bound with the constitutionalism. The Constitution must not be the Constitutionalism. Although the concept of constitutionalism derived of the Constitution, and its development even encourage the existence of constitutional state, the essence of constitutionalism are the the power limitation of the state. The Constitutionalism build a limited State, in order to the application of state and government are not arbitrary and is clearly expressed and regulated in the articles of the Constitution.